Analysis of Technical Efficiency and the Influence of Socioeconomic Factors on Oil Palm Farming in Muaro Jambi District - Indonesia - Fitri, Yanuar (International Journal of Environment, Agriculture and Biotechnology, 2023)
Technical efficiency and socioeconomic factors have a significant effect on the productivity of oil palm farming. Therefore, this study aimed to analyze technical efficiency and the influence of socio-economic factors on oil palm farming. Sampling was conducted using the Simple Random Sampling method. The data used are primary data and secondary data. The analysis method used is descriptive analysis and Stochastic Frontier production function analysis with MLE method. The results showed that the average land area of farmers in oil palm plantations was 3.9 ha with an average productivity of 14,638 kg/ha. Production factors that have a significant effect on production are land area, NPK fertilizer, Urea fertilizer and Dolomite. While those that do not have a significant effect are labor and herbicides. The level of technical efficiency achieved was the lowest 0.81 and the highest 0.95 and with an average of 0.86> 0.62 which means that farming is technically efficient. Socio-economic factors such as variables of age and distance from the farm to the farmer's house have the potential to reduce technical inefficiency but have no significant effect and variables that have a significant effect are variables of experience, education, and activeness in farmer groups while factors that increase technical inefficiency that have a significant effect are variables of land area.